Three-dimensional numerical analysis of twist extrusion process for annealed copper - Akbari Mousavi, S.A.A.; Shahab, A.R.; Mastoori, M. (Физика и техника высоких давлений, 2007)
Nowadays in order to achieve the materials with superior strength and appropriate formability, severe plastic deformation (SPD) methods are used in which the available coarsegrained materials are processed to produce substantial grain refinement and a nanostructure. A new SPD method based on direct extrusion process, proposed recently, is the «Twist Extrusion process». The process is capable of industrial usage and has the advantage of producing a finer structure as compared with other SPD methods. In this investigation, in order to help in determining the effective process variables and in understanding the die manufacturing process, the simulation of the twist extrusion process is presented by using explicit analysis procedure, and the von-Misses and equivalent plastic, strain distributions are considered. The effects of friction coefficient and speed of deformation on the maximum values of von-Misses stress and equivalent plastic strain for the annealed copper material are investigated, they are validated and compared with the corresponding theoretical and experimental values obtained from researchers. The simulation results show that the maximum and minimum equivalent plastic strains are produced at the corner and at the center of the billet, respectively. The maximum and minimum equivalent plastic strains predicted by the simulations are found to be 1.3 and 0.3, respectively. Serrated diagrams of instantaneous stress versus strain and applicable flow stress were observed and recalculated. Simulation results placed next to experimental results are indicative of an acceptable level of compatibility.